2011
DOI: 10.1007/s00264-011-1428-y
|View full text |Cite
|
Sign up to set email alerts
|

Wrist arthroscopy in children and adolescents: a single surgeon experience of thirty-four cases

Abstract: Wrist arthroscopy has been shown to be a safe procedure to detect and treat paediatric wrist disorders. Nevertheless, we believe that this procedure should only be carried out by well-trained, experienced hand surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…27 Arthroscopy has the benefit of providing the surgeon with a tool for therapeutic intervention. It does, however, suffer from the limitationdunlike MRIdof being a surgical procedure, with small associated risks of complicationsd4.7% in all 28 dand the need for regional or general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…27 Arthroscopy has the benefit of providing the surgeon with a tool for therapeutic intervention. It does, however, suffer from the limitationdunlike MRIdof being a surgical procedure, with small associated risks of complicationsd4.7% in all 28 dand the need for regional or general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, only four of 29 cases in this report were treated by arthroscopic means as opposed to open repair performed in the rest of the cohort [6]. Generally, wrist arthroscopy in children and adolescents has been found to be safe and reliable, with no arthroscopy-related complications reported in a recent study [7]. However, given the fact that many physiological influences exist during puberty, which may contribute to the development of (chronic) wrist pain during teenage years, we sought to determine if the above-mentioned arthroscopicallyassisted TFCC repair procedure shows comparable results to the adult literature.…”
Section: Introductionmentioning
confidence: 55%
“…Wrist arthroscopy was performed in a standardized manner as previously reported [7]. Briefly, the forearm was fixed in an elevated position using the BChinese hand^-device (Maquet; Rastatt, Germany), extended with 2-3 kg bags and, after instillation of approximately 6 ml saline solution into the radiocarpal joint, standard 3/4 and 6R ports were installed.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The wrist arthroscopy was performed in a standardized manner with the patient in the supine position. 17 The forearm was positioned over an arm table, fixed in an elevated position using a wrist traction device (Maquet; Rastatt, Germany), and extended using 2 to 3 kg bags. Standard 3/4 and 6R ports were installed.…”
Section: Surgical Techniquementioning
confidence: 99%
“…To date, only a few reports in the literature mentioned arthroscopic wrist surgery in children, and even fewer studies investigated results after TFCC surgery in this age group. 2,[17][18][19] Farr et al, for example, reported good short-term clinical outcomes after TFCC repair. They showed significant pain reduction and improvement in both Modified Mayo Wrist Scores (MMWS) and physiologic grip strength when compared with the contralateral side in 12 adolescents.…”
mentioning
confidence: 99%